Bottlenecks, remoteness and admixture shape genetic variation in island populations of Atlantic and Mediterranean common kestrels Falco tinnunculus. (22nd October 2018) - Kangas, Veli‐Matti; Carrillo, José; Debray, Paul; Kvist, Laura
Abstract : We studied genetic diversity and differentiation in island and nearby continental populations of a bird of prey, the common kestrel Falco tinnunculus . We sampled 11 islands in the eastern North Atlantic (Madeira and Canary Islands) and western Mediterranean archipelagos (Balearic Islands) and two continental sites (Iberian Peninsula and north‐west Africa). We used microsatellite (9 loci, n = 470) and mitochondrial data (cytochrome b sequences, n = 244) and applied Bayesian clustering, multivariate frequentist statistics and coalescence analyses. We revealed two main genetic clusters; the first including populations from the Atlantic islands and the second comprising populations from the Balearic Islands, the Iberian Peninsula and north‐west Africa, with additional finer scale structuring. The highest levels of genetic variation were found in Iberian Peninsula, north‐west Africa and Lanzarote island. The lowest diversity was detected in La Palma, the most north‐westerly island of the Canary Islands. The lowest levels of haplotype and nucleotide diversity were observed in Madeira and Gran Canaria and the highest in Menorca. We found evidence of decreasing genetic diversity with increasing severity of a past population bottleneck and, to some extent, with increasing geographic distance from the continent. The two Canary Island subspecies, F. t. dacotiae and F. t. canariensis, have diverged from each other to some degree and from the continental and Balearic conspecifics of F. t. tinnunculus . Samples from Madeira, representing F. t. canariensis, indicated affinities to both Canary Islands and Mediterranean clusters, depending on the marker and methods applied. Our results suggest stronger gene flow between close islands than between distant islands. The genetic structure of an endemic subspecies F. t. dacotiae in the easternmost Canary Islands is suggested to have an origin in a past hybridization between continental F. t. tinnunculus and insular F. t. canariensis .